A peculiar VNTR in the cystathionine Î²-synthase gene is a risk factor for Down Syndrome - Salemi, M; Barone, C; Romano, C; Salluzzo, M G; Giambirtone, M; Morale, M C; Calogero, A E; Grillo, L; Bosco, P; Romano, C (Cellular and Molecular Biology, 2015)
In the present study, we analysed a 31bp variable number of tandem repeats (VNTR) of the cystathionine Î²-synthase (CBS) gene in 427 subjects: 127 patients with Down syndrome (DS) and in 60 of their mothers; 172 age-and sex-matched controls and in 68 of their mothers. A significant statistical difference in the distribution of the 21 repeat allele was found comparing mothers of subjects with DS versus mothers of children without DS (Ï‡2= 4.166; P = 0.0413; Table 2). Since CBS 21 repeats allele carriers show a decrease of CBS enzyme activity possibly leading to lower intracellular glutathione concentration, these results could be explained by a higher not disjunction probability of chromosome 21 in oocytes, due to poor antioxidative protection against reactive oxygen species (ROS) toxic activity.